A characterization of the Copeland solution - Sanver, Mert Remzi (My University, 2010)
We show that the Copeland solution is equivalent to the minisum principle which requires to choose the candidate(s) who beat all remaining contenders in the smallest total number of steps. © 2010 Elsevier B.V.
Keywords: Copeland; Minisum; Tournament